Chinese-Finnish Economic Relations within the Arctic Context:Hopes and Disappointments - Stępień, Adam; Koivurova, Timo; Käpylä, Juha; Mikkola, Harri; Nojonen, Matti (Brill Nijhoff, 2020)
The chapter focuses on economic relations between China and Finland in the Arctic context. This is done from two perspectives. First, the chapter considers Chinese investments and presence in northern Finland and particularly Lapland. Relevant sectors include bioeconomy and tourism, the Arctic railway project, as well as – in terms of future prospects – mining, renewable energy, data centres and testing facilities. Second, the chapter looks at the instances of economic cooperation – Finnish investments in China, Chinese in Finland and joint ventures – in areas of Finnish Arctic expertise.